Functional validation of metabolic genes that distinguish Gleason 3 from Gleason 4 prostate cancer foci. Issue 15 (10th September 2019) - Roberto, Domenica; Selvarajah, Shamini; Park, Paul C.; Berman, David; Venkateswaran, Vasundara
Abstract: Background: Gleason grade is among the most powerful clinicopathological classification systems used to assess risk of lethal potential in prostate cancer, yet its biologic basis is poorly understood. Notably, pure low‐grade cancers, comprised predominantly of Gleason pattern 3 (G3) are typically indolent, with lethal potential emerging with the progression of higher‐grade Gleason patterns 4 (G4) or 5. One of the hallmarks of more aggressive cancer phenotypes is the stereotyped set of metabolic characteristics that transformed cells acquire to facilitate unregulated growth. In the present study, we profiled expression signatures of metabolic genes that are differentially expressed between G3 and G4 cancer foci and investigated the functional role of two of the profiled genes, PGRMC1 and HSD17B4, in prostate cancer cells. Methods: Gene expression profiling was conducted using 32 G3 and 32 G4 cancer foci from patients with 3+3 and ≥4+3 tumors, respectively. A 95‐gene Nanostring probe set was used to probe genes associated with energy metabolism. Two out of five genes ( PGRMC 1 and HSD17B4 ) that significantly distinguish between G3 and G4 were functionally validated in vitro using established prostate cancer cells (PC3, DU145). Expression of PGRMC1 and HSD17B4 was knocked down and subsequent studies were performed to analyze cell proliferation, migration, invasion, and apoptosis. Mechanistic studies that explored the epidermal growth factor receptor (EGFR) pathway were performed by Western blot. Results: Multivariate analysis identified five metabolic genes that were differentially expressed between G3 and G4 stroma ( P  < .05). Functional validation studies revealed that knockdown of PGRMC1 and HSD17B4 significantly decreased cell proliferation, migration, and invasion, and increased apoptosis in PC3 and DU145 cells. Mechanistic studies showed that these effects, after PGRMC1 knockdown, were possibly mediated through alterations in downstream components of the EGFR, protein kinase B, and nuclear factor kappa‐light‐chain‐enhancer of activated B cells pathways. Conclusion: The following study provides evidence supporting the use of metabolic genes PGRMC1 and HSD17B4 as a prognostic biomarker for the distinction between G3 and G4 prostate cancers.